Combined Conceptual-DFT, Quantitative MEP Analysis, and Molecular Docking Study of Benzodiazepine Analogs - Djebaili, Rachida; Melkemi, Nadjib; Kenouche, Samir; Daoud, Ismail; Bouachrine, Mohammed; Hazhazi, Halima; Salah, Toufik (Orbital: The Electronic Journal of Chemistry, 2021)
In the present work, a combined approach based on conceptual-DFT formalism and molecular docking simulations were performed to investigate the chemical reactivity of six Benzodiazepine analogs. Chemical reactivity descriptors derived from the conceptual DFT were determined and discussed to explain the global and local reactivity of the six studied analogs. Also, long-range interactions were studied using the quantitative analyses of molecular electrostatic potential (MEP) on van der Waals surface to identify the nucleophilic and electrophilic sites. Moreover, a statistical analysis was performed to assess the robustness of atomic charges to the basis set. The results revealed that Hirshfeld population analysis (HPA) was the most efficient for this purpose. Molecular docking simulations were performed to predict the binding affinities of the issued molecules and estimate the binding poses into four binding sites, three of them were recently discovered, located in GABAA receptor.DOI: http://dx.doi.org/10.17807/orbital.v13i4.1607